تقييم استخدام مزيج الكيتامين - بروبوفول والكيتامين لوحده في التركين لعملية تجريف الرحم - سليمان طارق (Latakia University Journal -Medical Sciences Series, 2018)
Objectives: To determine the efficacy of the admixture (ketofol) ketamine-propofol, recovery time, and adverse reactions of intravenous (IV) mixed 1:2 ketamine–propofol for adult procedural sedation and analgesia in patients undergoing currettage. Background: Use of analgesic drug combinations with differing mechanisms of action may provide additive or even synergistic effects with respect to improving pain control and facilitating the recovery process. Propofol is a sedative-hypnotic agent. rapid onset, short duration of action, and causes a dose-dependent respiratory depression and hypotension. Ketamine causes cardiovascular and respiratory stimulation, and analgesia, recovery agitation and vomiting, the use of ketofol may cause hemodynamic stability and analgesia afforded by ketamine, while minimizing recovery time by reducing the total amount of ketamine required for adequate sedation. As well, it is possible that lower initial and total doses of propofol may be associated with lower incidences of hypoxia and apnea. Recovery agitation, a common effect with the use of ketamine alone and nausea appear to be blunted by the sedative and antinauseant actions of propofol. This potential balance of effects has led us favor ketofol in combination over either agent alone. Material and methods: This prospective, randomized, controlled study was conducted on 150 women in the Obestetric Univercity Hosbital , ASA 1, aged 20-45 years, undergoing currettage. They were randomly allocated to two groups: group A (75 patient) receive only Ketamine and group B (75 patient) receive ketofol ( 1:2 ). we recorded all data: Vital signs before curettage and every 5 minutes until 30 minutes . Results: This research demonstrates that: there is vascular stability in the patients who received the admixture better than the others, in order to that , the sedation is better, and the adverse reactions are lesser. And that is combatible with international Researches conclusion: we conclude that the sedation and analgesia of the admixture is better from that of Ketamine Group, and its adverse reactions also are little, so we advise using the mixture. خلفية البحث وأهميته: إن استعمال التراكيب الدوائية المسكنة, ذات آلية التأثير المختلفة عن بعضها, يعطي بالتالي تأثيرات داعمة أو تآزرية فيما بين هذه الأدوية, علاوة على ذلك, تتحسن درجة السيطرة على الألم. إن البروبوفول هو دواء منوم ومركن, قصير أمد التأثير يحدث تثبيطاً تنفسياً, وهبوطاً في الضغط مرتبطاً بالجرعة, بينما يعتبر الكيتامين حاثاً للعضلة القلبية والجهاز التنفسي ( لكنه يحدث تثبيطاً تنفسياً عابراً ), كما أنه مسكن, وله تأثيراته الجانبية الأخرى ( الأهلاسات, الغثيان, الإلعاب, الرأرأة, زيادة المقوية العضلية.......) إن استعمال المزيج كيتامين- بروبوفول ( كيتوفول ), سيؤدي إلي استقرار الضغط والنبض (استقرار هيموديناميكي ), كما أنه سيؤدي بنفس الوقت, إلى إنقاص جرعة كل منهما, فإنقاص جرعة الكيتامين, سيؤدي بالتالي, إلى إنقاص التركيز البلاسمي الذروي منه, ويؤدي ذلك بالتالي إلى إضعاف التأثيرات الجانبية المذكورة سابقاً. كذلك يؤدي إنقاص جرعة البروبوفول, إلي إضعاف تأثيراته الجانبية أيضاً, فتقل شدة التثبيط التنفسي, والقلبي. ويحدث تأثير متعاكس بين الكيتامين والبروبوفول (يلغي تأثير أحدهما الآخر نوعاً ما )على الاقياء والضغط والنبض. إن هذه الفوائد الحاصلة من المزيج, أعطت البحث أهميته, خاصة وأنه يندرج في إطار طريقة التسكين والتركين ذات الطرق المختلفة, بهدف الوصول إلى التسكين والتركين المثالي, والتقليل قدر الإمكان من التأثيرات الجانبية الحاصلة. مواد البحث وطرقه: أجري البحث على 150 مريضة, أعمارهن ( 20 – 45 سنة ), ASA 1 , مقبولة من قبل أطباء التوليد والنساء, لإجراء تجريف الرحم , في مشفى التوليد الجامعي, تم اختيارهن بشكل عشوائي, نصفهن (المجموعة A) أعطين الكيتامين فقط , والنصف الاّخر ( المجموعة B ) أعطين (الكيتوفول ( 1:2) أي كل 1 مل منه يحوي 1 ملغ كيتامين و 2 ملغ من البروبوفول ), في دراسة عشوائية تداخلية استباقية مضبوطة, وسجلنا المراقبات التالية ( الضغط, النبض, التأثيرات الجانبية ) بفواصل 5 دقائق من الحقن وحتى نصف ساعة . نتائج البحث والمناقشة: أظهر البحث حدوث استقرار في هيموديناميكية المريضات, اللاتي تلقين الكيتوفول مع تركين كاف للعمل الجراحي, مع تأثيرات جانبية, أقل مما حدث عند المريضات اللاتي تلقين الكيتامين فقط ,حيث كانت تغيرات الضغط والنبض ضئيلة, كما لاحظنا انخفاض نسبة حدوث الأهلاسات وهذا يتوافق مع الدراسات العالمية. الاستنتاج والتوصيات: نستنتج أن المزيج أفضل من حيث الفعالية وأقل تأثيرات جانبية , إضافة إلى أنه يسمح لنا باستعمال جرعات قليلة من كلا الدواءين لذلك نوصي باستعمال هذا المزيج.